Farm animal metabolism and nutrition : critical reviews - D'Mello, J. P. Felix (CABI Publishing, 2000)
This text presents specially commissioned reviews of topics in farm animal metabolism and nutrition, where major advances have recently been made or which continue to represent issues of significance for students and researchers. Authors include researcers from Europe, North America and Australia.